The role of herd behaviour in determining the investor's Monday irrationality - Rayenda Khresna, Brahmana; Chee, Wooi Hooy; Zamri, Bin Ahmad (Penerbit Universiti Sains Malaysia, 2012)
With regards to determining whether herding is spontaneous and irrational behaviour causing the Day-of-the-week anomaly, this paper intersects the Christie and Huang (1995) herd behaviour model with French's (1980) Day-of-the-week model in several layers of tests. We use firm-level data and investigate the return dispersion of 846 Bursa Malaysia stocks during 1990–2010. This paper found the herd behaviour is the determinant for investor’s Monday irrationality, especially in small caps industry.